STRATEGI PENGEMBANGAN UMKM RIZQI BATIK BERBASIS PENTAHELIX DENGAN MENGGUNAAKAN ANALISIS SWOT DAN MATRIKS QSPM - Arip Nugraha, Junjun; Hana Kartini Sudrajat (LPPM IAIT, 2025)
UMKM Rizqi Batik is one of the creative industry players in Tasikmalaya City, which has potential to develop at the national and international levels. To support this growth, development strategies that consider internal strengths, external challenges, and multi-stakeholder collaboration are needed. This research aims to: (1) determine the internal and external conditions of UMKM Rizqi Batik in 2025, (2) map the strategic position of the business based on the SWOT approach within the framework of The Strategy-Formulation Analytical Framework (TSFAF), (3) formulate development alternative strategies involving Pentahelix actors, and (4) determine priority strategies based on objective assessment through the Quantitative Strategic Planning Matrix (QSPM) method. This research uses a descriptive method with a quantitative approach. Data collection techniques include observation, interviews, questionnaires, and documentation. Strategy analysis is conducted in three stages of TSFAF: Input Stage (using IFE, EFE, VRIO, Value Chain, PESTEL, and Porter's Five Forces analysis), Matching Stage (SWOT analysis and IE Matrix), and Decision Stage (strategy assessment using QSPM). The results show that Rizqi Batik has high internal strengths (IFE score of 3.07) and is capable of responding well to external opportunities (EFE score of 3.00), thus positioned in Quadrant I of the IE Matrix, which recommends an aggressive strategy. Three alternative strategies were generated from SWOT Matching, namely: (1) digital promotion based on cultural narratives, (2) market expansion through partnerships and online distribution, and (3) development of modern fashion products with batik motifs. Based on QSPM results, the digital promotion strategy received the highest Total Attractiveness Score of 9.9151 and was established as the priority strategy. The success of strategy implementation heavily depends on the synergy among the five main actors in the Pentahelix approach: academia, business actors, community, government, and media